Case Report: Implementasi Terapi Genggam Bola Karet Dalam Asuhan Keperawatan Pada Pasien Lansia Dengan Stroke - Dea Estri Nurrani; Nina Dwi Lestari (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Background: Stroke is a disorder caused by dysfunction of the blood supply to the brain which is divided into hemorrhagic subdivisions which are conceptualized as rupture of the cerebral blood vessels, and ischemia which appears in the blood circulation. Stroke can cause muscle weakness or coordination of body movements. Rubber ball grip exercise stimulates an increase in neuromuscular and muscular chemical activity. This will stimulate the limb muscle nerve fibers, especially the parasympathetic nerves to produce acetylcholine, resulting in contractions that can increase muscle strength. Objective: To apply a rubber ball hand-held exercise intervention to the muscle strength of the elderly with stroke. Methods: The method used in writing is a case report with the intervention of holding rubber ball exercises in the elderly with strokes who experience muscle weakness, carried out for 3 days. Results: The results of this case study show that after holding the rubber ball exercise intervention for 3 days, muscle strength can increase from a scale of 2 to 3. Conclusion: Rubber ball grip exercise is effective for increasing muscle strength in elderly patients with stroke